2013
DOI: 10.1073/pnas.1306477110
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic bacteria appear to mediate hyena social odors

Abstract: All animals harbor beneficial microbes. One way these microbes can benefit their animal hosts is by increasing the diversity and efficacy of communication signals available to the hosts. The fermentation hypothesis for mammalian chemical communication posits that bacteria in the scent glands of mammals generate odorous metabolites used by their hosts for communication and that variation in host chemical signals is a product of underlying variation in the bacterial communities inhabiting the scent glands. An ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 45 publications
(67 reference statements)
5
172
0
1
Order By: Relevance
“…[5,6]); nonetheless, there is growing recognition of reproductive signalling via olfactory channels [7]. As in several non-primate species [8][9][10], olfactory cues of pregnancy occur in humans, possibly facilitating mother-infant recognition [11]; otherwise, the potential for olfactory gestational cues in primates has been ignored. Here, we investigate pregnancy effects on olfactory cues in a promiscuous, non-human primate, the ring-tailed lemur (Lemur catta).…”
Section: Introductionmentioning
confidence: 99%
“…[5,6]); nonetheless, there is growing recognition of reproductive signalling via olfactory channels [7]. As in several non-primate species [8][9][10], olfactory cues of pregnancy occur in humans, possibly facilitating mother-infant recognition [11]; otherwise, the potential for olfactory gestational cues in primates has been ignored. Here, we investigate pregnancy effects on olfactory cues in a promiscuous, non-human primate, the ring-tailed lemur (Lemur catta).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research to understand the complex microbial communities living in or on multicellular organisms (termed the microbiome) has sparked fundamental changes in our understanding of the biology of metazoans (1)(2)(3)(4)(5). The microbiome can affect host health directly by influencing metabolism (6), development (7), inflammation (8), or behavior (9), but it may also influence host health indirectly through interactions with infectious pathogens. The microbiome may interact with pathogens through competition for resources, release of antimicrobial compounds, contactdependent antagonism, or modulation of the host immune response (10), and an "imbalanced" microbiome may leave the host more susceptible to pathogen infection (11,12).…”
mentioning
confidence: 99%
“…More recent cultivationindependent studies of spotted hyaenas (Crocuta crocuta) and striped hyaenas (Hyaena hyaena) showed that the bacterial and SCFA profiles of the two hyaena species differ and that the two profiles covary within each hyaena species. Further, among spotted hyaenas, the two profiles are social group-specific, and reflect sex and reproductive state among members of the same social group [49][50][51]. Similar patterns are evident among mammals that communicate via urine marking as well.…”
Section: Chemosensory Detection Of Microbial Productsmentioning
confidence: 82%